A NEW SPECIES OF ZEUGOPHORA KUNZ~ FROM JAVA (COLEOPTERA: CHRYSOMELIDAE: MEGALOPODINAE) - REID, C. A.M. (TREUBIA, 1992)
Zeugophora javana sp, n. is described from West Java and placed in the subgenus Pedrillia. Diagnostic characters are given to separate Z. javana from other species in Australia.